Middle East respiratory syndrome coronavirus vaccines: current status and novel approaches - Okba, Nisreen MA (Curr Opin Virol, 2017)
Middle East respiratory syndrome coronavirus (MERS-CoV) is a cause of severe respiratory infection in humans, specifically the elderly and people with comorbidities. The re-emergence of lethal coronaviruses calls for international collaboration to produce coronavirus vaccines, which are still lacking to date. Ongoing efforts to develop MERS-CoV vaccines should consider the different target populations (dromedary camels and humans) and the correlates of protection. Extending on our current knowledge of MERS, vaccination of dromedary camels to induce mucosal immunity could be a promising approach to diminish MERS-CoV transmission to humans. In addition, it is equally important to develop vaccines for humans that induce broader reactivity against various coronaviruses to be prepared for a potential next CoV outbreak.